Self-Navigating Field Programmable Gate Array Robot - Pierson, Kim W.; Howard, Turner; Zaleski, Marissa; Tollakson, Rebecca (My University, 2018)
The purpose of this research is to design a self-navigating robot that can perform at a higher speed than the previous configuration. We accomplished this by using a new kind of computer chip called a field programmable gate array (FPGA).
Color poster with text, graphs, and images.
Keywords: Self-navigating robot; Coding; LabVIEW; Electronics; Robotics; Posters